Strategi Percepatan Adopsi Teknologi Usahatani Kedelai Dalam Mendukung Swasembada Pangan Nasional - Rawung, Jefny Markus; Indrasti, Rita; Hutapea, Ronald T.P (Jurnal Penelitian Pertanian Tanaman Pangan, 2019)
Soybean ICT was designed base on success story of rice field ICT experience. The research aim to describe farmers opportunity of technology adoption accelerationin case study of Soybean ICMin South Sulawesi. The research has done in FY 2015, with 30 adopters participants as respondent. Data analysis uses binary logistic regression approach which lag adoption as dependent variable and others 12 variables as independent variable, namely: ages, formal education base, land property status, farming system scale, distance from nearest information source and information pathway. The research reveals that: (1) Threre were variation of farmer appreciation of soybean technology, (2) Technology adoption lag as acceleration proxy, shown about 1 – 4 years since he knows technology to technology adoption, (3) There are 5 partial independent variable influence of adoption acceleration, namely farm size, long distance of farm location to house, IATAD, technology source, and land status, (4) opportunity of soybean farmers occur one time if there are adding soybean harvest for 1 hectar. 6’s time for farm location wich more close to house farmers. In other hand, farmers adoption gradually occur since distance location of farm tend relatively far to technology information source. The technology guidance with participative and market price policy for acceleration of adoption innovation, are needed.